The path made clear - Winfrey, Oprah (Bluebird, 2019)
Everyone has a purpose. And, according to Oprah Winfrey, 'Your real job in life is to figure out as soon as possible what that is, who you are meant to be, and begin to honour your calling in the best way possible.' That journey starts right here. In her book, The Path Made Clear, Oprah shares what she sees as a guide for activating your deepest vision of yourself, offering the framework for creating not just a life of success, but one of significance. The book's ten chapters are organised to help you recognize the important milestones along the road to self-discovery, laying out what you really need in order to achieve personal contentment, and what life's detours are there to teach us. Oprah opens each chapter by sharing her own key lessons and the personal stories that helped set the course for her best life. She then brings together wisdom and insights from luminaries in a wide array of fields, inspiring readers to consider what they're meant to do in the world and how to pursue it with passion and focus.Renowned figures such as Ellen DeGeneres, Lin-Manuel Miranda, Brene Brown, Elizabeth Gilbert, Eckhart Tolle and Jay-Z share the greatest lessons from their own journeys toward a life filled with purpose. Paired with over one hundred awe-inspiring photographs to help illuminate the wisdom of these messages, The Path Made Clear provides a beautiful resource for achieving a life lived in service of your calling - whatever it may be.